Efektifitas Sistem Informasi Manajemen Bagi Pengguna Internal (Studi Kasus Pada PT Bank Lampung) - Alhibarsyah Alhibarsyah (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
To fulfill information needs that are relevant, fast, and accurate, the application of information technology, especially computer-based is inseparable from the role of the three basic components of a computer. The success model of the information technology system developed by DeLone & McLean quickly received a response. PT. Bank Lampung as one of the banking service providers in Lampung, is the object of research to determine how variables affect the level of Quality System, Information Quality, Service Quality, Use and Satisfaction and Use of Benefits, to determine the level of effectiveness in PT Bank Lampung's internal customer management information system. SEM (Structural Equation Modeling) is a multivariate statistical technique that is a combination of factor analysis and regression analysis (correlation), which aims to examine the relationship between variables in the model. To explain the overall relationship that exists between the variables in this study using AMOS software (Moment Structure Analysis). This shows that the sample variance-covariance matrix (observation data) I s the same as the estimated matrix of variance-covariance (population) based on the model built, it is expected that the results of this study KI significantly influence P, KI significantly affects KP, KS influences significant impact on P, significantly affecting KS KP, KL significantly affected P, KL significantly affected KP, P significantly affected KP, P significantly affected M, KP significantly affected M.